Antibiotic residues in milk: Past, present, and future - Sachi, Sabbya; Ferdous, Jannatul; Sikder, Mahmudul Hasan; Hussani, SM Azizul Karim (Journal of Advanced Veterinary and Animal Research, 2019)
Now-a-days, various types of antibiotics are being used worldwide in veterinary sector indiscriminately for promotion of growth and treatment of the livestock. Significant portions of antibiotics are released through milk of dairy animals unaltered and exert serious harmful effects on human health. This review evaluates and compare researches on antibiotic residues in milk in published literatures from Pubmed, CrossRef, CAB direct, DOAJ, JournalTOCs, AGRICOLA, ScientificGate, Electronic Journals Library, CAB abstracts, Global Health Databases, Global Impact Factor, Google Scholar, Park Directory of Open Access Journals, BanglaJOL and ISC E-Journals. Antibiotics residue in milk was first detected in 60s and then with an increasing trend with highest after 2,000 (188). The highest no. of works, 49 (21.87%) were accomplished in China, followed by Spain, 30 (13.39%); Germany, 11 (4.91%); and USA, 10 (4.46%). Continent-wise highest researches are published from Europe, 105 (46.88%), followed by Asia, 77 (34.38%); South America, 18 (8.04%); North America, 16 (7.14%); and Africa, 8 (3.57%). For detection, Bovine milk sample is mostly used, 193 (86.16%), followed by ovine, 19 (8.48%); and caprine, 14 (6.25%). Acetonitrile was used in maximum cases (77) for processing the samples. Chromatographic technique was the highest, 115 (51.34%) for detection. Residue of β-lactam group have been detected mostly 133 (36.54%), followed by tetracyclines, 51 (14.01%); fluoroquinolones, 49 (13.46%); sulfonamides, 46 (12.64%); and aminoglycosides, 38 (10.44%). This review observe that antibiotics residues are more common in milk samples that are being manifested in increasing researches on antibiotic detection and measures should adopt to cease this residue. J. Adv. Vet. Anim. Res., 6(3): 315-332, September 2019